MODIFICATION OF THE LEONTIEV MODEL FOR DESCRIPTION OF REGIONAL ECONOMIC CLUSTERS - S. O. Kramarov; N. V. Pelikhov; L. V. Sakharova; V. V. Khramov (Вестник университета, 2020)
It has been proposed to use a new analogue of the Leontiev model of interindustry balance as a mathematical apparatus for studying the influence of clustering on the financial and economic state of enterprises (organizations). For the basic concept used for the mathematical formalization of the problem, the economic potentials of enterprises, calculated on the basis of fuzzy aggregation of heterogeneous complexes of parameters, have been selected. The authors proceeded from the need to implement the third mission of the university – to promote the social, cultural and economic development of society, in whichthese educational institutions operate through the creation, implementation, expansion, dissemination and use of new knowledge, establishing direct relationships with the region and all its components, which, in turn, it serves as the basis for the development of education itself, based on projects to solve real problems. The contribution of universities to the process of formation and development of clusters is considered as a process of implementing intellectual potential.